2006
DOI: 10.1002/fld.1391
|View full text |Cite
|
Sign up to set email alerts
|

Baroclinic stability for a family of two‐level, semi‐implicit numerical methods for the 3D shallow water equations

Abstract: SUMMARYThe baroclinic stability of a family of two time-level, semi-implicit schemes for the 3D hydrostatic, Boussinesq Navier-Stokes equations (i.e. the shallow water equations), which originate from the TRIM model of Casulli and Cheng (Int. J. Numer. Methods Fluids 1992; 15:629-648), is examined in a simple 2D horizontal-vertical domain. It is demonstrated that existing mass-conservative low-dissipation semiimplicit methods, which are unconditionally stable in the inviscid limit for barotropic flows, are uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The hydrodynamic model Si3D is based on Computational Fluid Dynamics and adopts an implicit finite‐difference method for numerical solution of the Navier‐Stokes equations. It has been comprehensively described [ Casulli and Cheng , ; Casulli and Cattani , ; Rueda et al ., ; Smith , ] and applied in many investigations of water flow in natural water bodies [e.g., Rueda et al ., ; Singleton et al ., ].…”
Section: Numerical Model Formulationmentioning
confidence: 99%
“…The hydrodynamic model Si3D is based on Computational Fluid Dynamics and adopts an implicit finite‐difference method for numerical solution of the Navier‐Stokes equations. It has been comprehensively described [ Casulli and Cheng , ; Casulli and Cattani , ; Rueda et al ., ; Smith , ] and applied in many investigations of water flow in natural water bodies [e.g., Rueda et al ., ; Singleton et al ., ].…”
Section: Numerical Model Formulationmentioning
confidence: 99%
“…The backward Euler time stepping in TRIM‐like methods has been shown to be baroclinically stable for baroclinic flow [ Rueda et al , 2007] but barotropically dissipative [ Casulli and Cattani , 1994]. It can be shown that the ratio of the reflected or transmitted surface wave energy to that of internal waves scales to sβ 1/2 for Ω 2 ≪ β [e.g., Hurley and Imberger , 1969].…”
Section: Comparison Between the Numerical And Analytical Resultsmentioning
confidence: 99%
“…The Si3D hydrodynamic model, a semi‐implicit 3‐D computational fluid dynamics code, was adopted in this study. The code employs a finite‐difference method for numerical solution of the Navier‐Stokes equations (Rueda & Schladow, ; Rueda et al, ). The governing equations include continuity equation, momentum equations, and scalar transport equations, which can be found in (Smith, ).…”
Section: Methodsmentioning
confidence: 99%